Systematic Country Diagnostic for Uzbekistan - World Bank (World Bank, Washington, DC, 2016)
This Systematic Country Diagnostic (SCD) explores how Uzbekistan can consolidate its recent achievements and accelerate progress on the twin goals of eradicating extreme poverty and promoting shared prosperity. The SCD is organized into five chapters. Chapter one frames the issues of poverty reduction and shared prosperity, and situates them in the context of Uzbekistan’s recent development. It reviews the status and drivers of progress in these areas, identifies analytical constraints, and highlights areas for further study. Chapter two describes the necessary conditions for sustaining rapid economic growth and robust quality job creation. It underscores the importance of expanding private-sector participation and investment in key economic sectors. Chapter three considers how a well-functioning labor market and access to essential public services can enhance the inclusiveness of growth. Chapter four analyzes threats to the sustainability of Uzbekistan’s recent gains over both the medium and the long term. Chapter five concludes by examining the constraints to growth and development revealed by the analysis, and it proposes a framework for prioritizing policy actions designed to address them.